A Water Vapor Sensor Application of Sn1-xFexO2-δ Fibers. Issue 1805 (11th September 2015) - Rodríguez, Juan Manuel; Watson, Amanda; Abrego, Ildeman; Ardisson, José Domingos; Samudio, Carlos Ariel; Ching-Prado, Eleicer Antonio
ABSTRACT: Tin oxide is of great interest due to their potential technological applications, such as: gas sensors, energy conversion, catalysts and others. Appropriate doping can further enhance the conductivity of the SnO2 material with little loss of transparency. Isolated tin iron oxide fibers (Sn1-x Fex O2-δ ) with x (molar %) = 0, 2, 4, 6, 8 and 10 were prepared by the electrospinning technique. Anhydrous SnCl4, FeCl3· 6H2 O, different alcohols, chloroform and a polymer (PEO) were used as precursor materials. Appropriate mixture of these reagents defines the deposition solution. The samples were deposited on glass substrates and annealed at 500 o C. The fibers are characterized by scanning electron microscopy (SEM), impedance spectroscopy and temperature dependence current-voltage measurements. The fibers with diameters between 2 to 12 microns were used for sensorial purpose. Thus, water vapor sensor responses were also measured and the experimental results are tested using the Freundlich isotherms model.